Transvesical route for NOTES urological applications: advances & controversies - Lima, E (2014)
Natural Orifice Transluminal Endoscopic Surgery (NOTES) has emerged recently in the experimental surgical field, innovating for the passage of luminal barrier, the absence of scars and reduction of post-operative pain. Among the various ports of access (transvaginal, transgastric, transvesical and transcolonic), this paper is an update on advances & controversies of transvesical port for NOTES Urological applications.